Place or Partisanship? The Conditional Role of Identities on Candidate Support. Issue 6 (November 2021) - Fudge, Daniel; Armaly, Miles T.
Recent work on the influence of social identities reveals that placed-based attachments serve as a powerful heuristic when making political assessments. When a politician makes a place-based appeal—such as cuing rural origins—individuals who share that identity more strongly support the candidate. Yet, other important identities—namely, partisanship—are strongly related to place. Here, we attempt to disentangle the unique influence of a place-based identity (and the strength thereof) on candidate support. Additionally, we ask whether shared place can compel supportive behavior, rather than merely increase expressive support. Using a unique survey experiment, we find that those who strongly identify with a place are more willing to donate to the campaign of a shared-place candidate, relative to weaker place identification, but only among co-partisans. We find little evidence that place attachment influences supportive behavior beyond the role of partisanship. Disparate identities—here, place and partisanship—that create cross-pressures can operate in tandem.